Antioxidant and Anti-Inflammatory Properties of Bee Products Potentially Reduce Oxidative Stress and Inflammation After Physical Activity/Exercise: A Systematic Review - Donny Ardy Kusuma; Mohamed Nashrudin Bin Naharudin; Cyuzuzo Callixte; Muhammad Aljunaid; Awang Firmansyah; Deby Tri Mario; Ilham; Anton Komaini; Novadri Ayubi (OVS LLC, 2023)
Study purpose. This research aims to analyze and highlight the potential of bee products in reducing oxidative stress and inflammation after physical activity/exercise. Materials and methods. This research uses a systematic review method by searching various journal databases such as Scopus, Web of Science, PubMed and Embase. The inclusion criteria in this study were articles published in the last 5 years and articles discussing bee products, honey, oxidative stress, inflammation, physical activity, and exercise. The exclusion criteria in this study were articles published in disreputable journals. Titles, abstracts, and full texts of articles were screened then verified and stored in Mendeley software. A total of 7,124 articles from the Scopus, Web of Science, PubMed and Embase databases were identified. A total of 8 articles that met the inclusion criteria were selected and analyzed for this systematic review. Results. Bee products that have anti-oxidant properties can reduce oxidative stress and the anti-inflammatory properties of bee products can reduce uncontrolled inflammation due to exercise. Conclusions. Bee products contain flavonoids which have anti-oxidant properties which can reduce oxidative stress. In addition, the anti-inflammatory properties of bee products can reduce uncontrolled inflammation due to physical activity/exercise. In this case, honey works by inhibiting inflammation through NF-κB signals and reducing inflammation by suppressing the secretion of pro-inflammatory cytokines such as TNF-α and inflammatory markers such as CRP. Reducing inflammation can reduce the intensity of muscle pain. It is recommended that bee products be used in individuals to reduce oxidative stress and inflammation after physical activity/exercise.